PENDIDIKAN KARAKTER DI MASYARAKAT - zainuri, ahmad (Conciencia, 2019)
Society (society) is a group of people who form a semi-closed (or semi-open) system, where most interactions are between individuals in the group. The variety of education received by students in this community is very much. These include the formation of habits, formation of knowledge, attitudes and interests, as well as moral and religious formation. Education in community education can be said to be indirect education, education carried out unconsciously by the community. And the students themselves consciously or not, they have educated themselves, strengthening their faith and self-confidence in the values ​​of morality and religion in society. That is, the community environment influences the development of students. The influence given by the environment is intentional and accidental. That is, the environment has no specific intentions in influencing the development of students. And the community environment is very influential for children's character development. If the child is in a good community environment, it will also have a good influence on the development of the child's character. Likewise, on the other hand a bad environment can also have a bad influence on children's character development. As parents, they must be smart and smart to choose a good environment for their children, because it will determine the child's character development. Character education as an effort to develop character is an effort made by the world of education to help students understand, care and act in accordance with ethical values. The purpose of character education is to form characters that are implemented in the subject's essential values ​​with the behaviors and attitudes they have. In this case the formation of character, there must be educational networks. Especially in information technology and telecommunications today, one of the factors that have a huge influence on development or vice versa is the destruction of the character of society or the nation is mass media, especially electronic media, with the main actors being television. Actually the magnitude of the role of the media, especially print and radio media, is in the development of national character. The mass media plays a dual role. On the one hand, playing public service advertisements or touching advertisements, on the other hand broadcasts programs/soap operas which actually show negative things, which ultimately are not shunned, instead imitated by the audience. The media must be controlled by the state. The state has an obligation to control all media activities, so that they are in accordance with the goals of the country itself. The legal instruments must be clear and fair. Indonesia itself has a Depkominfo, but only regulates frequency policies, broadcasting rights, and so on. More specifically, there is the Indonesian Broadcasting Commission (KPI), which was formed more independently, but recognized by the government. KPI is expected to be able to filter media activities (especially television) to suit the country's goals, norms, culture, customs, and of course religion. However, until now, the KPI is considered to be still quite weak in acting (filtering), and so than that, it is very necessary (strength) of the participation of the community in controlling these media.